Bibliometric and visual analysis of miRNAs in heart diseases from 2004 to 2023 - Jin, Ying; Duan, Jingqi; Yin, Qiaoxiang; Ma, Yanmin; Lou, Jingli; Zhang, Wei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMicroRNAs (miRNAs) add a new dimension to HD forecast, diagnosis, and therapy based on the potential applications. The miRNA-related research in the heart disease (HD) field has received close attention in the past two decades. However, there is a lack of studies that comprehensively and objectively analyze the current situation of miRNA application in the HD field using the bibliometrics method.ObjectiveTo comprehensively analyze the global scientific outputs of miRNAs in HD research from 2004 to 2023.MethodsAll the articles and reviews of miRNA-related research in the HD field were retrieved using the Web of Science core collection (WOSCC) title search, and bibliometric analysis was performed in Microsoft Excel 2019, CiteSpace, VOSviewer, and Bibliometrics (R-Tool of R-Studio).Results3,874 publications were included in the bibliometric analysis. Collaborative network analysis indicates that China with the maximum number of publications (2,063) and the USA with the highest total citations (59,331) are influential countries in this field. Peking Union Medical College is the most prolific university with the maximum publications (134), and the University of California System is the most authoritative institution regarding betweenness centrality (0.27). PLOS ONE tops the journal list of publications, closely followed by the International Journal of Molecular Sciences and Scientific Reports with more than 100 articles. Considering the number of publications, citations, and total link strength overall, Olson. Eric N, Van Rooij Eva, Thum Thomas, Yang Baofeng, Wang Kun; and Lu Yanjie are authoritative authors in this field. The expression changes and regulatory mechanisms of specific miRNAs in various heart biological and pathophysiological processes have been the continuous research hotspots. “exosomes”, “extracellular vesicles”, “autophagy”, and “management” have been novel hot research topics since 2018, which focused on the diagnosis and treatment of HD. The current research development trend is how to translate the achievement of miRNA-related diagnosis and therapeutic drugs for HD into the clinic.ConclusionOur study revealed the intellectual structure of miRNA in HD research, which may help scholars understand this field comprehensively and find partners.